Evolution of late glacial ice-marginal lakes on the northwestern Canadian Shield and their influence on the location of the Dubawnt Lake palaeo-ice stream. - Stokes, C.R.; Clark, C.D. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2004)
During deglaciation of the North American Laurentide Ice Sheet large proglacial lakes developed in positions where proglacial drainage was impeded by the ice margin. For some of these lakes, it is known that subsequent drainage had an abrupt and widespread impact on North Atlantic Ocean circulation and climate, but less is known about the impact that the lakes exerted on ice sheet dynamics. This paper reports palaeogeographic reconstructions of the evolution of proglacial lakes during deglaciation across the northwestern Canadian Shield, covering an area in excess of 1,000,000 km2 as the ice sheet retreated some 600 km. The interactions between proglacial lakes and ice sheet flow are explored, with a particular emphasis on whether the disposition of lakes may have influenced the location of the Dubawnt Lake ice stream. This ice stream falls outside the existing paradigm for ice streams in the Laurentide Ice Sheet because it did not operate over fined-grained till or lie in a topographic trough. Ice margin positions and a digital elevation model are utilised to predict the geometry and depth of proglacial lakes impounded at the margin at 30-km increments during deglaciation. Palaeogeographic reconstructions match well with previous independent estimates of lake coverage inferred from field evidence, and results suggest that the development of a deep lake in the Thelon drainage basin may have been influential in initiating the ice stream by inducing calving, drawing down ice and triggering fast ice flow. This is the only location alongside this sector of the ice sheet where large (>3000 km2), deep lakes (not, vert, similar120 m) are impounded for a significant length of time and exactly matches the location of the ice stream. It is speculated that the commencement of calving at the ice sheet margin may have taken the system beyond a threshold and was sufficient to trigger rapid motion but that once initiated, calving processes and losses were insignificant to the functioning of the ice stream. It is thus concluded that proglacial lakes are likely to have been an important control on ice sheet dynamics during deglaciation of the Laurentide Ice Sheet.